CLINICAL AND BIOCHEMICAL DESCRIPTION OF PREMATURE INFANTS WITH EXTREMELY LOW AND VERY LOW BIRTH WEIGHT - I. V. Mikhalenko; E. V. Mikhalev; S. P. Ermolenko (Педиатрическая фармакология)
The purpose of this work was to study the levels of neurotrophic factor nerve growth of the brain, the levels of vascular endothelial growth factor, the levels of neurospecific enolase and the activity of endothelin-1 in the serum of blood in preterm infants with extremely low birth weight in association with the state of the cerebral circulation, and morphologic changes in the brain. We examined 60 preterm infants, which were divided into two groups depending on weight at birth. In neonates with extremely low birth weight the dysfunction of mechanism of autoregulation in cerebral blood flow was characterized by a decrease in blood flow velocities in the anterior cerebral and in the basilar arteries, in association with low levels of trophic factors in serum to month of life and the developments of degenerative changes in the brain. In neonates with very low birth weight infants in the early neonatal period the vasospasm of cerebral vessels with the activity of neurotrophic factors to month of life gave way to the stabilization of the cerebral hemodynamics.